Down in the dumpster [large type] - Davis, Page M.; Davis, Susan Page (Davis, Page M. Dumpster diva, 2026)
"You never know what you'll find in a dumpster. If Cassie had known the misadventures she'd get into at her stopgap job, she would have kept checking the help-wanted ads. With her crabby dispatcher hounding her, she collects the rubbish from a senior citizens' complex in her garbage truck. When she empties the dumpster, a witness sees a body fall into her compactor. How will she explain this to Mac? And just as important, can rubbish and romance mix?"--